Medical faculty's perception of students' mental health: - Vitor Mendonca; Aecio Gois (Anales de la Facultad de Medicina)
This study sought to explore the perspective of medical faculty on the mental health of their students. This qualitative study based on a focus group is part of a longitudinal research that studied the mental health of Brazilian students. One group was conducted with faculty employed at a medical school. Topics discussed covered the concept of mental health and medical education. Six professors participated in one group. The mental health of medical students is a construct that encompasses emotional aspects, ability to solve problems and multiple facets of a human being, according to the participants. Artistic practices, moments of socialization and leisure were perceived as stimulating students' good mental health. Excessive demands generate competitiveness and the teacher's expectation of the student's good performance based on their own experience can harm the student's mental health. Participants also highlighted that a pedagogical reformulation that makes sense for the student's learning process is necessary to update traditional curricula. Medical students’ mental health is influenced by experiences and exchanges during the medical school, mainly between professor and student, understood as necessary and inherent to the process of becoming physician. The findings of this study show the need for curriculum changes in the medical education process and updating teacher training for good practices that reinforce good mental health.